Persepsi Konsumen Muslim terhadap Sertifikasi Halal pada De Dapoer Rhadana Hotel Kuta Bali - Astutik, Nur Dwi; Mawardi, Ahmad Ahsin Kusuma; Mahardiyanto, Agus (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
De Dapoer-Rhadana Hotel Kuta Bali is one of the restaurants that has been certified halal in its products. As consumers especially muslim consumers should be more vigilants, selective and observant in choosing restaurants while in Bali that are halal to eat and thayyib. The method used is this study is qualitative descriptive that aims to know the muslim consumer